2021
DOI: 10.2139/ssrn.3767901
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum, Risk Factors, and Outcomes of Neurological and Psychiatric Complications of COVID-19: A UK-Wide Cross-Sectional Surveillance Study

Abstract: SARS-CoV-2 is associated with new-onset neurological and psychiatric conditions. Detailed clinical data, including factors associated with recovery, are lacking, hampering prediction modelling and targeted therapeutic interventions.In a UK-wide cross-sectional surveillance study of adult hospitalised patients during the first COVID-19 wave, with multi-professional input from general and sub-specialty neurologists, psychiatrists, stroke physicians, and intensivists, we captured detailed data on demographics, ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
3
6
0
Order By: Relevance
“…The neurological and psychiatric manifestations of COVID-19 have been reported in several studies in adults (age 18 years or older). 3 , 4 , 5 Similarities between our study and the adult CoroNerve cohort 25 include the range of disorders identified; although stroke prevalence was much higher in adults, present in almost half of the cases. Adults were also more likely to have multiple neurological diagnoses (13% of adult cases) than children and adolescents, perhaps suggesting there are multiple mechanisms linked to underlying risk factors and comorbidities.…”
Section: Discussionsupporting
confidence: 70%
“…The neurological and psychiatric manifestations of COVID-19 have been reported in several studies in adults (age 18 years or older). 3 , 4 , 5 Similarities between our study and the adult CoroNerve cohort 25 include the range of disorders identified; although stroke prevalence was much higher in adults, present in almost half of the cases. Adults were also more likely to have multiple neurological diagnoses (13% of adult cases) than children and adolescents, perhaps suggesting there are multiple mechanisms linked to underlying risk factors and comorbidities.…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, all domains of β 2 GPI have been described as targeted by antiphospholipid antibody, but the most clinically significant to date is antibodies to domain I [30] . The delayed presentation, in our case, is consistent with the recent description of a biphasic presentation of encephalopathy, with the delayed phase (approximately 20-days) reported as more severe [31] . The exact mechanism is unclear, and could be immune-mediated.…”
Section: Discussionsupporting
confidence: 91%
“…It is known that psychiatric illness, delirium, encephalopathy and encephalitis may complicate COVID-19 [4,5], and potential biomarkers exist to support these diagnoses alongside imaging changes [6]. In this patient, however, multiple negative SARS-CoV-2 PCR tests made this diagnosis less likely, although an asymptomatic COVID-19infection around the time of vaccination cannot be excluded.…”
Section: Table 1 Summary Of Investigationsmentioning
confidence: 81%